P125 Sleep and fear conditioning, extinction learning and extinction recall: a systematic review and meta-analysis of polysomnographic findings. (7th October 2021) - Schenker, M; Ney, L; Miller, L; Felmingham, K; Nicholas, C; Jordan, A
Abstract: Sleep may contribute to the long-lasting consolidation and processing of emotional memories. Experimental fear conditioning and extinction paradigms model the development, maintenance, and treatment of anxiety disorders. The literature provides compelling evidence for the involvement of rapid eye movement (REM) sleep in the consolidation of such memories. This meta-analysis correlated polysomnographic sleep findings with psychophysiological reactivity to the danger (CS+) and safety stimuli (CS-), to clarify the specific role of sleep stages before and after fear conditioning, extinction learning and extinction recall. Overall, there was evidence that more pre-learning sleep stage two and less slow wave sleep was associated with higher psychophysiological reactivity to the safety stimulus during extinction learning. Preliminary evidence found here support the role of REM sleep during the post-extinction consolidation sleep phase in clinical populations with disrupted sleep, but not in healthy controls. Furthermore, the meta-regressions found that sex moderated the associations between sleep and psychophysiological reactivity throughout the paradigm providing evidence for diverging correlations in male and females. Specifically, increased post-extinction REM was associated with poorer extinction and safety recall in females while the opposite was found in males. These results have implications for future research in the role of sleep in emotional memory processing.